Antibiofilm potential of plant extracts: inhibiting oral microorganisms and Streptococcus mutans - Bartels, Nomi; Argyropoulou, Aikaterini; Al-Ahmad, Ali; Hellwig, Elmar; Skaltsounis, Alexios Leandros; Wittmer, Annette; Vach, Kirstin; Karygianni, Lamprini (Frontiers in Dental Medicine, 2025)
IntroductionA range of disinfectant mouthwashes are available for oral hygiene. The gold standard is Chlorhexidine digluconate (CHX), which, like other available products, cannot be used without side effects in the long term. However, in recent years, therapy with herbal products, often considered antiquated, has regained considerable interest. Therefore, the search for plant compounds as an alternative to existing oral disinfectants is meaningful.MethodsIn this study, eleven Mediterranean plant extracts were tested for their antimicrobial effect in vitro. Methanol extracts of the following plants were produced by the pharmaceutical faculty of the University of Athens: Mentha aquatica, Mentha longifolia, Sideritis euboea, Sideritis syriaca, Stachys spinosa, Satureja parnassica, Satureja thymbra, Lavandula stoechas, Achillea taygetea, Phlomis cretica, and Vaccinium myrtillus. The extracts were dissolved for microdilution experiments at concentrations ranging from 10 to 0.019 mg/ml. The oral pathogens tested were Streptococcus mutans, Streptococcus oralis, Streptococcus sobrinus, Prevotella intermedia, Fusobacterium nucleatum, Parvimonas micra, Porphyromonas gingivalis, and Candida albicans. Enterococcus faecalis, Staphylococcus aureus, and Escherichia coli were used as references.ResultsAll extracts, except the methanol extract of V. myrtillus, showed an antibacterial effect at concentrations ranging from 10 to 0.15 mg/ml. None of the extracts exhibited a significant antifungal effect. In general, the anaerobic pathogens could be inhibited and killed at lower concentrations compared to the aerobic pathogens. S. oralis also showed good susceptibility to the extracts. Additionally, the extracts' ability to inhibit biofilm formation by S. mutans was tested. L. stoechas at a concentration of 0.3 mg/ml showed a moderate inhibitory effect. The extracts of L. stoechas, S. thymbra, S. parnassica, and the methanol extract of V. myrtillus were effective at concentrations up to 1.25 mg/ml. P. cretica was able to inhibit and kill S. mutans at a concentration of 0.6 mg/ml, but its effectiveness in biofilm inhibition significantly decreased at 2.5 mg/ml.DiscussionThe study's hypothesis that all extracts would exhibit an antimicrobial effect was thus confirmed.